2001
DOI: 10.1890/0012-9615(2001)071[0117:codcba]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Diet Choice by a Small Generalist Herbivore

Abstract: We examined the energy, nutrient, time, and habitat consequences of diet choice by a generalist herbivore, the hispid cotton rat (Sigmodon hispidus) on the Texas coastal prairie. Benefit–cost and linear programming models were developed and used to test several specific hypotheses about diet choice, foraging strategy, and habitat use by cotton rats. Within cotton rat habitat, there were significant differences among both seasons and habitat patches in the abundance and biomass of foods available. Monocot patch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
32
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 88 publications
2
32
0
Order By: Relevance
“…An explanation can be derived from results of foraging experiments in laboratory enclosures provisioned with stands of natural dietary items. Video tracking revealed that foraging movements by hispid cotton rats were nearly linear in these experiments (Randolph and Cameron 2001). Results from these feeding trials and the T/S analysis indicate that reproductive females forage in mixed patches by directed, linear movements.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…An explanation can be derived from results of foraging experiments in laboratory enclosures provisioned with stands of natural dietary items. Video tracking revealed that foraging movements by hispid cotton rats were nearly linear in these experiments (Randolph and Cameron 2001). Results from these feeding trials and the T/S analysis indicate that reproductive females forage in mixed patches by directed, linear movements.…”
Section: Discussionmentioning
confidence: 55%
“…In the current study, females preferred mixed habitats and avoided dicot habitats, whereas males showed no habitat preference. The importance of mixed habitats to reproductive females is underscored by the fact that their home ranges contained a higher proportion of mixed habitat than was available (Cameron and Spencer 1985) and they rely on a mixed diet of monocots and dicots (Randolph and Cameron 2001). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations